The Public Relations Strategy of the Bogor City Council Secretariat in Carrying Out Instagram Content Activities @setwankotabogor - Jahro, Anisa Alifah; Astuti, Vivien Febri (IJESS International Journal of Education and Social Science, 2025)
This study aims to analyze the strategies implemented by the Public Relations of the Bogor City DPRD Secretariat in managing the Instagram content of @Setwankotabogor. The method used is descriptive qualitative with interviews as the data collection technique. The results of the study indicate that the Public Relations of the Bogor City DPRD uses Instagram to increase transparency and a positive image of the institution. The Public Relations team coordinates in creating content and adapts themes to emerging local issues. However, the main challenges faced are limited creative ideas and low interaction from the audience. Recommendations given are to increase content creativity, interaction with the audience, and further support from the organization.